The traveling heads 2.0: multicenter reproducibility of quantitative imaging methods at 7 tesla - Voelker, Maximilian N.; Kraff, Oliver; Görke, Steffen; Laun, Frederik B.; Hanspach, Jannis; Pine, Kerrin J.; Ehses, Philipp; Zaiss, Moritz; Liebert, Andrzej; Straub, Sina; Eckstein, Korbinian; Robinson, Simon; et al. (NeuroImage, 2021)
Object - This study evaluates inter-site and intra-site reproducibility at ten different 7 T sites for quantitative brain imaging. - Material and Methods - Two subjects - termed the “traveling heads” - were imaged at ten different 7 T sites with a harmonized quantitative brain MR imaging protocol. In conjunction with the system calibration, MP2RAGE, QSM, CEST and multi-parametric mapping/relaxometry were examined. - Results - Quantitative measurements with MP2RAGE showed very high reproducibility across sites and subjects, and errors were in concordance with previous results and other field strengths. QSM had high inter-site reproducibility for relevant subcortical volumes. CEST imaging revealed systematic differences between the sites, but reproducibility was comparable to results in the literature. Relaxometry had also very high agreement between sites, but due to the high sensitivity, differences caused by different applications of the B1 calibration of the two RF coil types used were observed. - Conclusion - Our results show that quantitative brain imaging can be performed with high reproducibility at 7 T and with similar reliability as found at 3 T for multicenter studies of the supratentorial brain.
Gesehen am 27.05.2021